Explaining specific taxes management and use in the health sector: a qualitative study - Mahdi Kooshkebaghi; Sara Emamgholipour; Hossein Dargahi (BMC, 2022)
Abstract Background and aim Being the major source of revenue and essential economic tool for policymakers to improve public health, taxes contribute to government spending on the development of health care facilities and services. Given the financial challenges facing the health sector together with the public health issues that affect each society, placing specific taxes on some goods, services, and activities can be effective in this regard. The study aims to explain the various dimensions of specific taxes in the health sector and management of these resources in order to achieve the health system goals. Materials and methods This study with a qualitative research design was conducted using semi-structured interviews with open-ended questions in 2020-2021. In total, 38 managers, policymakers, economists, key experts, and other individuals, as informants, were interviewed. Purposive and snowball with maximum variation was also employed. As well, content analysis was utilized to shed light on the data. The transcribed interviews were further imported into MAXQDA for extracting and classifying the relevant codes. Findings In this study, 5 main themes and 23 subthemes were labeled. The main themes accordingly included "Objectives and Conditions of Specific Health Taxes", "Earmarked Taxes", "Taxes on Goods and Measures of Harmful to Health", "Value-Added Taxes", and "Green Taxes". Discussion and conclusion Considering the specific taxes in the health sector, i.e., taxes on goods and measures of harmful to health, value-added taxes, and green taxes, all taxation and pricing policies need to take account of the effects as well as the advantages and disadvantages of types of taxes, a country's economic structure, the conditions of industries and manufacturing enterprises, cultural aspects in society, and peoples' socioeconomic status.